UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN KEDONDONG HUTAN (Spondias pinnata (L.F.) Kurz.) DENGAN BERBAGAI METODE UJI - Suhaimi Azizah; Nursamsiar Nursamsiar; Syamsu Nur (Jurnal Ilmiah Manuntung, 2019)
The leaf of kedondong hutan (Spondias pinnata (L.F.) Kurz.) Contain of flavonoid compound, which capable as antioxidants that function for preventing free radicals. The purpose of this study was to determine the antioxidant activity profile of ethanol extract of kedondong hutan leaf with DPPH, ABTS radical and iron reduction methode (FRAP). This study used experimental research with stages of sample collection, plant determination, simplicia preparation, maceration with 70% ethanol, phytochemical screening and antioxidant activity assay with UV-Vis spectrophotometry. The results obtained from the ethanol extract of kedondong hutan leaves had antioxidant activity on DPPH and ABTS with IC50 of 32.83 ppm and 45.84 ppm respectively. In FRAP method kedondong hutan leaves had antioxidant activity which is equivalent to quarcetin of 2936.7 µmol QR /g sample. Ethanol extract of kedondong hutan leaves has very strong antioxidant power against DPPH, ABTS radical and iron reduction.